2005
DOI: 10.1002/ajmg.b.30151
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin receptor 2C (HTR2C) and schizophrenia: Examination of possible medication and genetic influences on expression levels

Abstract: The serotonin receptor 2C (HTR2C) gene is of interest in schizophrenia due to its involvement in regulation of dopamine activity in the prefrontal cortex. We have previously reported a decreased expression of HTR2C mRNA levels in the prefrontal cortex of schizophrenia patients. The variability in mRNA expression levels is evaluated here more closely in relation to promoter haplotypes and neuroleptic treatment received by the patients. The decrease in HTR2C mRNA was present in neuroleptic treated individuals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…It indicated that expression of a subset of genes was dramatically downregulated in the hippocampus of Dgcr8 +/-mice. Interestingly, some of them, such as Klotho (Nagai et al, 2003;Kachiwala et al, 2005;Shiozaki et al, 2008;Semba et al, 2014), Ttr (Goodman, 1998;Huang et al, 2006;Brouillette and Quirion, 2008;Fleming et al, 2009;Benoit et al, 2011), Sulf1 (Narayan et al, 2008;Kalus et al, 2009), and Htrc2 (Masellis et al, 1998;Castensson et al, 2005;Iwamoto et al, 2009;Wright et al, 2013), have been known to be deeply involved in cognition or psychiatric diseases, which seems to support the validity of our gene array data. Nevertheless, the reduced expression of Igf2 mostly Figure 2 Spontaneous alternation Y-maze task after intrahippocampal administration of PBS or IGF2.…”
Section: Decline Of Igf2 In the Hippocampus Of Dgcr8 +/-Micesupporting
confidence: 74%
“…It indicated that expression of a subset of genes was dramatically downregulated in the hippocampus of Dgcr8 +/-mice. Interestingly, some of them, such as Klotho (Nagai et al, 2003;Kachiwala et al, 2005;Shiozaki et al, 2008;Semba et al, 2014), Ttr (Goodman, 1998;Huang et al, 2006;Brouillette and Quirion, 2008;Fleming et al, 2009;Benoit et al, 2011), Sulf1 (Narayan et al, 2008;Kalus et al, 2009), and Htrc2 (Masellis et al, 1998;Castensson et al, 2005;Iwamoto et al, 2009;Wright et al, 2013), have been known to be deeply involved in cognition or psychiatric diseases, which seems to support the validity of our gene array data. Nevertheless, the reduced expression of Igf2 mostly Figure 2 Spontaneous alternation Y-maze task after intrahippocampal administration of PBS or IGF2.…”
Section: Decline Of Igf2 In the Hippocampus Of Dgcr8 +/-Micesupporting
confidence: 74%
“…One of these RNA species -snoRNA-115 regulates alternative splicing of serotonin receptor 2C gene (HTR2C) [82]. Genetic variation in HTR2C gene has been associated with obesity [83], schizophrenia [84] and antipsychoticinduced weight gain [85].…”
Section: Parent-of-origin Effects and Schizophreniamentioning
confidence: 99%
“…Promoter haplotypes of HTR2C have been repeatedly reported to affect HTR2C expression in in vitro reporter assay, [51][52][53][54][55] although there is no evidence that these can influence HTR2C expression in brain. 56 The 3' region of exon 5 in HTR2C and subsequent intronic region called exon complementary sequence (ECS), both of which forms dsRNA loop recognized by ADARs. These regions are critical for RNA editing and highly conserved among mammals, and no polymorphism was reported in human.…”
Section: Effect Of Genetic Variations Of Htr2c On Expression and Rna mentioning
confidence: 99%